Globalization, Brain Drain, and Development - Docquier, Frédéric; Rapoport, Hillel (Journal of Economic Literature, 2012)
This paper reviews four decades of economics research on the brain drain, with a focus on recent contributions and on development issues. We first assess the magnitude, intensity, and determinants of the brain drain, showing that brain drain (or high-skill) migration is becoming a dominant pattern of international migration and a major aspect of globalization. We then use a stylized growth model to analyze the various channels through which a brain drain affects the sending countries and review the evidence on these channels. The recent empirical literature shows that high-skill emigration need not deplete a country's human capital stock and can generate positive network externalities. Three case studies are also considered: the African medical brain drain, the exodus of European scientists to the United States, and the role of the Indian diaspora in the development of India's information technology sector. We conclude with a discussion of the implications of the analysis for education, immigration, and international taxation policies in a global context. (JEL F02, F22, J24, J61, O15)